Hierarchical Spatial Decisions in Fragmented Landscapes: Modeling the Foraging Movements of Woodpeckers - Vergara-Egert, P; Perez-Hernandez, C; Soto-Gonzalez, G (Elsevier, 2015)
The ability of animals to collect and use environmental information in fragmented landscapes may considerably decrease as the spatial scale at which they search for feeding resources increases. Here, we used an individual-based model to assess the scale-dependent movement patterns of woodpeckers when searching for their main foraging resources (wood-boring larvae). Two movement strategies for woodpeckers were compared in simulated landscapes where resources were spatially clustered at two hierarchical levels (trees and forest patches): (1) "top-down" foragers, whose movement decisions respond primarily to memorized information on forest patches; and (2) "bottom-up" foragers with random, purely exploratory movements that result from tree-scale foraging experiences. Top-down foragers were able to find more resources than bottom-up foragers, except in landscapes with very few and poor quality patches. Thus, the combined use of spatial memory and random exploration should considerably benefit woodpeckers that forage in landscapes with low fragmentation levels. Contrary to our expectations, bottom-up foragers had larger connectivity values by visiting more patches across the landscape. Thus, model results support the idea that as the landscape becomes fragmented the home-range size of woodpeckers increases. We conclude that landscape planning must aim at maintaining habitat quality and quantity above critical thresholds below which woodpeckers both lack enough resources and the ability to make efficient use of memory-based decisions. © 2015 Elsevier B.V.